Human Resource Management Innovation In Improving Talent Retention In The Generation Z Era - HM, Usman (Pasundan Social Science Development, 2025)
This study aims to understand how Generation Z talents interpret various innovations in Human Resource Management (HRM) in their workplace, and how this influences their decision to stay or leave the organization. Using a descriptive qualitative approach with a phenomenological case study design, the study was conducted in three organizations in different sectors that have adopted HRM innovations. A total of 15 Generation Z employees (aged 22–27 years) were interviewed in depth to explore their experiences. The analysis revealed five main themes: empowering flexibility, relevant and personalized learning, inclusive work culture, continuous recognition and feedback, and attention to holistic well-being. The findings show that HRM innovations that are authentic and in line with Generation Z values ??can increase their sense of appreciation and engagement with the organization, thus positively impacting retention. This study provides practical insights for HR leaders and practitioners to create more innovative, adaptive, and employee-focused HRM strategies, especially in dealing with the dynamics of the Generation Z workforce in Indonesia.